Traversing Situations and Contexts in Networked Learning: The Role of Situated Readiness in Business Education - Wilson, Stephanie; Wardak, Dewa (Proceedings of the International Conference on Networked Learning, 2024)
To meet the goals of business education and develop responsible business leaders, educators need to design networked learning environments that nurture and leverage connections. This includes connecting students to each other, their teachers, to industry and to the community. This paper aims to understand factors that support or inhibit students’ participation in networked learning in a business education context. Productive participation in learning networks is essential if students are to connect meaningfully with people and resources in ways that support their learning and experience. As the physical and digital learning environments students engage in often include complex configurations of tools, tasks, and epistemic resources, they require the skills and dispositions to effectively transition between these environments. Using a situated readiness framework by Hachmann and Dohn (2018), this study presents an analysis of focus group data from business students in higher education to identify ways in which students’ level of readiness impacts on their ability to participate effectively in learning networks. Students in the present study highlighted a range of challenges they faced when attempting to traverse between face-to-face and online learning environments. However, our study also revealed numerous other situations or contexts that business students needed to traverse as part of their networked learning experience. These were grouped into five overarching categories: domain; space and configuration; format, structure and resources; people or groups; and purpose and responsibility. Overlayed onto the situated readiness framework, these categories can be used by other researchers to gain a more nuanced understanding of how students navigate the complexities of networked learning environments. Future research conducted across a range of learning contexts would allow the categories to be refined and built upon. The study also identified skills and dispositions that contributed to students' level of readiness to navigate situations and contexts within networked learning environments, and some preliminary design considerations based on the findings. To support business students in higher education on their journey to becoming responsible business leaders, it is imperative that they are able to participate productively in complex networked learning environments. As educators, this requires us to understand their level of readiness to do so and equip them with the skills and dispositions they need to participate effectively.